2019
DOI: 10.1111/aor.13521
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term physiological response to high‐frequency‐actuated pVAD support

Abstract: Ventricular assist devices (VADs) are an established treatment option for heart failure (HF). However, the devices are often plagued by material‐related hemocompatibility issues. In contrast to continuous flow VADs with high shear stresses, pulsatile VADs (pVADs) offer the potential for an endothelial cell coating that promises to prevent many adverse events caused by an insufficient hemocompatibility. However, their size and weight often precludes their intracorporeal implantation. A reduction of the pump bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…For the high‐speed measurements (dynamic measurements) the same two strain sensors were used and the heart phantom connected to a custom‐built bellows actuator. [ 49,50 ] The actuator was comprised of a polytetrafluorethylene (PTFE) bellows (ElringKlinger AG, Dettingen/Erms, Germany) that could be compressed/stretched through a voice coil (Moticont, Van Nuys, CA, USA) in order to provide a volume displacement (of up to 65 mL). The actuator and, hence, the bellows were driven by a sinusoidal reference signal, allowing the implementation of volume changes (between 10 and 30 mL), as well as, a range of physiological heart rates (60, 80, and 100 bpm).…”
Section: Methodsmentioning
confidence: 99%
“…For the high‐speed measurements (dynamic measurements) the same two strain sensors were used and the heart phantom connected to a custom‐built bellows actuator. [ 49,50 ] The actuator was comprised of a polytetrafluorethylene (PTFE) bellows (ElringKlinger AG, Dettingen/Erms, Germany) that could be compressed/stretched through a voice coil (Moticont, Van Nuys, CA, USA) in order to provide a volume displacement (of up to 65 mL). The actuator and, hence, the bellows were driven by a sinusoidal reference signal, allowing the implementation of volume changes (between 10 and 30 mL), as well as, a range of physiological heart rates (60, 80, and 100 bpm).…”
Section: Methodsmentioning
confidence: 99%
“…Two separate studies have investigated pulsatile VADs operated at frequencies that exceed the heart rate. 29,30 The in silico and in vitro results demonstrated that pulsatility remains sufficiently high despite the high frequency of operation. In all, the present work is a unique example of a converging approach in which engineering and biological requirements are considered together during the design phase.…”
Section: The Hyperelastic Membrane Design and Validationmentioning
confidence: 98%
“…Mathias Rebholz et al of ETH Zurich, Zurich, Switzerland presented data on their pulsatile ventricular assist device (pVAD) system consisting of a pump and an actuator specifically designed for actuation frequencies of up to 240 bpm. In vitro and in vivo results of the short‐term reaction of the cardiovascular system show no significant changes in left ventricular and aortic pressure between actuation frequencies from 60 to 240 bpm.…”
Section: Cardiac Support and Blood Pumpsmentioning
confidence: 99%